Twenty Thousand Leagues Under the Sea - Verne, Jules (New Delhi: Fingerprint Press, 2022)
The sea is the be all and end all! . . . It's an immense wilderness where a man is never lonely, because he feels life astir on every side.After several maritime casualties and many vessels spotting a mysterious monstrous creature in the waters, the United States government arranges for an expedition to chase and destroy this creature. Pierre Aronnax, a professor at the Paris Museum and his faithful servant Conseil, join the others aboard the Abraham Lincoln and set out on their search. As a series of adventures follows, will they be able to find this sea monster?One of the debut adventure novels, 20,000 Leagues Under the Sea is Jules Verne s masterpiece. Published more than a century ago, this classic science fiction continues to be praised by its readers.
Keywords: Fiction and Literature